Resourcefulness and Resilience: The Experience of Personal Recovery for Mothers with a Mental Illness. (24th November 2017) - Hine, Rochelle; Maybery, Darryl; Goodyear, Melinda
Abstract: Understanding of key characteristics and processes of personal recovery from mental illness is growing. However, a paucity of research exists with mothers with mental illness around experiences of personal recovery. An improved understanding of the interplay between illness, parenting and broader social factors may better inform how mental health services respond to the needs of these women. Using constructivist grounded theory (CGT), in-depth interviews were conducted with seventeen women who were mothers with a mental illness, residing in Australia. Through the CGT technique of constant comparative analysis, initial codes were synthesised and theoretical sampling employed to reach saturation of the categories associated with the construct of personal recovery. For mothers with a mental illness, personal recovery takes place within and is shaped by broader social contexts. Six key dimensions of personal recovery were 'recognising recovery', 'mothering', 'experiencing oppression', 'managing distress', 'making a change' and 'feeling better'. This study found that mothers with mental illness interpret recovery as enduring through difficult times, rather than a process of personal transformation and adjustment which is articulated within personal recovery literature. Well-being outcomes for women with children may be more effectively promoted through strategies that address underlying factors such as supporting early mothering, preventing violence against women, addressing trauma, and redressing socio-economic disadvantage and gender disparity.